The impact of high temperatures on Vitis vinifera cv. Semillon grapevine performance and berry ripening - Greer, Dennis H. (Frontiers in Plant Science, 2013)
The heat event that occurred in many parts of Australia in 2009 was the worst on record for the past decade, with air temperatures exceeding 40oC for 14 days. Our aim was to assess the impacts of this heat event on vine performance, including ripening, yield and gas exchange of Vitis vinifera cv. Semillon grown in a Riverina vineyard. To assess the affect of high temperatures on Semillon grapevines, the vines were covered with a protective layer to reduce radiant heating and were compared with vines exposed to ambient conditions. The heat event had major effects on ripening; reducing the rate by 50% and delaying harvest ripeness and causing a high incidence of berry shrivel and sunburn. Yield was not affected. Photosynthesis was reduced 35% by the heat event while transpiration increased nearly 3-fold and was accounted for by increased stomatal conductance. The conclusion of this study was that heat events delayed ripening in Semillon berries and caused a significant reduction in berry quality. Strategies to minimise the radiant load during heat events are required and this study has confirmed a protective layer can reduce canopy temperatures and enhance berry quality.